Bridging Between Information Retrieval and Databases PROMISE Winter School 2013, Bressanone, Italy, February 4-8, 2013. Revised Tutorial Lectures - Ferro, Nicola.; Ferro, Nicola. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2014)
The research domains of information retrieval and databases have traditionally adopted different approaches to information management. However, in recent years, there has been an increasing cross-fertilization among the two fields and now many research challenges are transversal to them. With this in mind, a winter school was organized in Bressanone, Italy, in February 2013, within the context of the EU-funded research project PROMISE (Participative Research Laboratory for Multimedia and Multilingual Information Systems Evaluation). PROMISE aimed at advancing the experimental evaluation of complex multimedia and multilingual information systems in order to support individuals, commercial entities, and communities, who design, develop, employ, and improve such complex systems. The overall goal of PROMISE was to deliver a unified environment collecting data, knowledge, tools, and methodologies, and to help the user community involved in experimental evaluation. This book constitutes the outcome of the PROMISE Winter School 2013 and contains 9 invited lectures from the research domains of information retrieval and databases plus short papers of the best student poster awards. A large variety of topics are covered, including databases, information retrieval, experimental evaluation, metrics and statistics, semantic search, keyword search in databases, semi-structured search, evaluation both in information retrieval and databases, crowdsourcing and social media.